Solidarity bridges: alternative food economies in urban Greece - Rakopoulos, Theodoros (The Greek Review of Social Research, 2018)
Set in the urban-rural continuum of Thessaloniki, this paper explores the grounded social activities of certain groups, committed to building a social economy of distributing food without intermediaries. In the light of new ethnographic data from grassroots responses to livelihoods’ hardship, I propose to expand reciprocity's conceptual boundaries, extended to include a local concept rampant in crisis-ridden Greece: solidarity. The solidarity economy can be seen as a conceptual and political bridge that symbolically as well as materially brings together communities of food production and consumption. The cosmology of the horio (village) is an unexpected urban activist metonym in the food distribution systems that have emerged amidst austerity measures in Greece.